Analysis and Treatment of Tannery Waste Water by using Combined Filtration and Coagulation Treatment Process: Treatment of Tannery Waste Water by Using Combined Filtration and Coagulation - Ahmed, Imran; Muddasar Habib; Habib, Unsia; Hai, Abdul; Khan, Amad Ullah (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2016)
Tannery waste water severely effects the quality of water bodies into which it is discharged. Tanning effluent contains organic matter, chromium (Cr) and solid waste such as fleshing, trimmings, shavings and buffing dust. About 60% of the total chromium salts react with hides while 40% of the chromium amount remains in the solid and liquid wastes, which makes it a potential environmental concern. In this research work, tannery waste is processed by the pre-treatment step using a filter media followed by post treatment coagulation process. The later step is analyzed using FeCl3 as a coagulant by varying chemical dose and settling time. These parameters were optimized to maximize the pollutant removal efficiencies measured in terms of reduction in concentration of Cr, total dissolve solids (TDS), total suspended solid (TSS), turbidity, biological oxygen demand (BOD5) and chemical oxygen demand (COD). It was observed that by using 150 mg/L coagulant dose with 24 hours settling time, maximum removal efficiency of 93 % Cr, 71 % TDS, 95 % TSS, 72 % turbidity, 81 % BOD and 85% COD was achieved. The hybrid treatment process, investigated experimentally, can be employed commercially as a pre-treatment step for tannery waste waters.